PERANCANGAN DAN UJI KUALITAS ALAT DESTILASI SEDERHANA SEBAGAI LANGKAH KREATIF MEWUJUDKAN KEMANDIRIAN LABORATORIUM - Okviyoandra Akhyar; Mohan Taufiq Mashuri (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
Designed and quality insurance of simple distillation apparatus as alternative way to solve lack of laboratory tools. Research about designed and quality controlled of simple distillation apparatus have been reported. Simple apparatus design’s applied principle of distillation method. Basically, distillation was used to separate the constituents of a mixture by using differences of boiling point. Simple distillation apparatus designed by using materials which is commonly used in daily life such as electric kettle , PVC, glass tube / plastic tube and any other easy to find material . Distillate that has been produced would be controlled by using Argentometry method . Based on the datas , simple distillation apparatus can be used as an alternative way for producing of distillate which could be used for daily laboratory purposes because there were no detected contamination of salt in distillates.